Proangiogenic factor midkine is increased in melanoma patients with sleep apnea and induces tumor cell proliferation. Issue 12 (15th October 2020) - Cubillos‐Zapata, Carolina; Martínez‐García, Miguel Ángel; Díaz‐García, Elena; Toledano, Victor; Campos‐Rodríguez, Francisco; Sánchez‐de‐la‐Torre, Manuel; Nagore, Eduardo; Martorell‐Calatayud, Antonio; Hernández Blasco, Luis; Pastor, Esther; Abad‐Capa, Jorge; Montserrat, Josep María; et al.
Abstract: Midkine (MDK) might mediate the proangiogenic effect of intermittent hypoxia (IH) in patients with obstructive sleep apnea (OSA) and cutaneous melanoma (CM). We compare circulating MDK in CM patients with and without OSA, and their relationship with tumor aggressiveness, while exploring in vitro effects of soluble MDK on human lymphatic endothelial (HLEC) and melanoma cell proliferation. In 360 CM patients, sleep studies and MDK serum level measurements were performed. The effect of MDK on cell proliferation was assessed using HLEC and melanoma cell lines with patient sera under both normoxia and IH. MDK levels were higher in severe OSA compared to mild OSA or non‐OSA patients, whereas no differences in VEGF levels emerged. In OSA patients, MDK levels correlated with nocturnal hypoxemia and CM mitotic rate. In vitro, MDK promotes HLEC proliferation under IH conditions. Moreover, cultures of the human melanoma cell line C81‐61 with sera from patients with the highest MDK levels promoted tumor cell proliferation, which was attenuated after the addition of MDK antibody. These responses were enhanced by IH exposures. In conclusion, in CM patients, OSA severity is associated with higher MDK levels, which, appear to enhance both the lymphangiogenesis as the intrinsic aggressiveness of CM tumor cells.